Pendampingan Inovasi Produk dan Pemasaran pada Kelompok Usaha Kue Ladrang Di Desa Karangsono Kecamatan Bangsalsari: Kabupaten Jember - Ifa, Khoirul (IMPOWERMENT SOCIETY, 2018)
This activity aims to develop product and marketing innovation in ladrang pastry business group in karangsono village sub district bangsalsari jember district so that the product has high competitiveness. The method of community service activity has several stages: (1) Survey: The survey activity will be conducted to see the business condition of the partner, (2) Interview: The purpose of the interview is to explore information related to the problems of the partner and also to find the solution, (3) packaging and product taste variance: The packaging innovation practice is assisted by lecturers by designing more attractive and unique packaging, while the taste variances are accompanied by lecturers, (4) Monitoring and evaluation: Monitoring and evaluation activities will be conducted periodically until partners can produce innovative products so that the target and outcome of this program can be achieved. The Target of Community Service Activities of this cake ladrang business group in Karangsono Village, Jember Regency are: (1) Market expansion, not only marketing in local village stalls but in nearby areas such as Lumajang. (2) Improvement of product quality both taste and packaging innovation.